Gambaran Citra Tubuh pada Remaja dengan Thalasemia - Neneng Vinna Angelina; Reni Nuryani; Sri Wulan Lindasari (Jurnal Gema Keperawatan, 2023)
Adolescents with thalassemia experience emotional feelings such as mood swings, and have more psychological, emotional, and social behavioral problems than healthy adolescents, at this age their abilities and development become better in participating in understanding their own health status. Thalassemia adolescents use their own point of view when assessing body shape, and even have a difficult task compared to ordinary adolescents who are looking for an identity at this age. The physical impact that occurs on Facies Cooley, is characterized by a protruding forehead, depression of the nasal bones, black skin, enlarged spleen, bone deformities, and short stature which can cause a disturbance of self-image. Adolescents at this age can solve simple problems, and work methods at a young age will be more focused so they don't make many mistakes when given simple tasks. This study aimed to describe body image in adolescents with thalassemia at Sumedang Hospital in 2023. This research method used a quantitative descriptive design, with a population of 47 adolescents with thalassemia. The sampling technique uses total sampling. The data collection instrument used was the Body Image Scale (BIS) questionnaire which had been modified by the author with a validity test result of 0.684 and Cronbach alpha reliability of 0,728. The results showed that most of the adolescent respondents with thalassemia had adequate body image, namely 36 respondents (76.6%), good body image of 5 respondents (10.7%), and poor body image of 6 respondents (12, 7%).